Systemic Fibrinolytic Therapy in the Presence of Absolute Contraindication; a Case Series - Pishgahi, Mahdi; Alirezaei, Toktam; Hajimoradi, Behzad; Nekooghadam, S.Mojtaba; Shahi, Shima (Archives of Academic Emergency Medicine, 2018)
In massive pulmonary embolism (PE), fibrinolytic therapy is a potential lifesaving treatment; therefore, if other treatments are not available, the physicians encounter this question: can we accept the risk of complications from fibrinolytic therapy, especially intracranial hemorrhage, in the presence of absolute contraindication, in order to save the patient’s life? Here, we describe three cases of massive PE with absolute contraindication for fibrinolytic therapy who presented to emergency department following dyspnea. Since, surgical or catheter embolectomy were not available and patients were very high risk for transferring to another hospital, systemic fibrinolytic was administered. The patients improved clinically and were discharged from hospital. It seems that, if no other acceptable treatments are available, physicians could consider fibrinolytic therapy, even at the presence of contraindication, to save the patient’s life.